Miss Sarah Jack of Spanish Town, Jamaica - Trollope, Anthony, 1815-1882 (Salt Lake City, UT : Project Gutenberg, 2003)
"Miss Sarah Jack of Spanish Town, Jamaica" by Anthony Trollope is a novel written in the mid-19th century during the Victorian era. The story explores the struggles of life in Jamaica, specifically focusing on the challenges faced by an English sugar grower, Maurice Cumming, as he navigates personal and commercial hardships in a decaying colonial environment. The novel intertwines themes of love, duty, and the socio-economic changes impacting the island. The narrative follows Maurice Cumming, who is burdened by the crumbling estate he inherited after the emancipation of slaves and the subsequent economic decline of the sugar industry. He is visited often by his wealthy and politically engaged aunt, Miss Sarah Jack, who pressures him to undertake a political role as a member of the colonial assembly. Maurice becomes infatuated with Marian Leslie, a young woman from a nearby estate known for her flirtatious nature. The dynamics of their relationship shift as Maurice grapples with his feelings and societal expectations, leading to both romantic and emotional turmoil. Ultimately, amidst the backdrop of colonial decline and personal struggles, Maurice's eventual confession of love to Marian marks a turning point in both their lives, influenced by the steadfast support of Miss Jack. The novel closes on a note of hope as Marian resolves to embrace a more serious relationship with Maurice, leaving behind her flirtatious ways. (This is an automatically generated summary.)
Release date is 2003-01-01
Transcribed from the 1864 Chapman & Hall (3z(BTales of All Countries(3y (Bedition by David Prices
Keywords: Short stories; Courtship -- Fiction; Jamaica -- Fiction